MENINGKATKAN LITERASI DIGITAL SISWA PADA MATA PELAJARAN IPA DENGAN MENGGUNAKAN MULTIMEDIA INTERAKTIF DI MTSN 3 ROKAN HULU - Dhoti, Shofi Ma’rifaturriya; Darmawati, Darmawati; Nikmah, Nikmah (Jurnal Manajemen Pendidikan, 2022)
Writing this article aims to improve students' digital literacy by using interactive multimedia in science learning, focusing on the structure and function of plant tissue at MTsN 3 Rokan Hulu. This study consisted of two meetings using innovative technology in the form of interactive multimedia with different sub-materials, namely (1) the structure and function of plant tissues in roots, stems and leaves, (2) the structure and function of plant tissues in flowers, fruits and seeds. Aspects of digital literacy that will be assessed in this study include: accessing, analyzing and evaluating, creating, reflecting, and communicating. This research is a qualitative research with descriptive method. Samples were taken by simple random sampling technique. The sample is class VIII students at MTsN 3 Rokan Hulu as many as 32 students. The results showed that learning science on the structure and function of plant tissue by using interactive multimedia could improve the digital literacy of junior high school students with an overall percentage difference of 4.00% from meeting 1 (70.33%) to meeting 2 (74.33%). . Thus, it can be concluded that the use of interactive multimedia can improve the digital literacy of students at MTsN 3 Rokan Hulu in terms of the structure and function of plant tissues. In the end, it is hoped that similar research can be carried out related to efforts to increase digital literacy with other materials.